Accounts receivable management among small and medium manufacturing firms in Kuching Sarawak - Anita, Hasli. (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The primary objective of the empirical study is to ascertain the explanatory variables for the collection of debts from accounts receivables among the small and medium size manufacturing firms in Kuching Division, Sarawak. The identification of significant variables and the relative importance of each predictor on the collection of debts from accounts receivables are dealt with by using Multiple Linear Regression Model. Therefore a set of cross sectional data for the year 1999 with a total of 65 observations was used as a sample data. Descriptive Statistics and Inferential Statistics were carried out towards the dependent and independent variables in the data analysis. The finding revealed that there were methods and techniques that exist on collection of debts from accounts receivables among the small and medium manufacturing firms in Kuching Sarawak. Among the determinants, partial payments provide the most significants impact on the collection of debts from accounts receivables. The results indicate that there do exist a variable that explains the collection of debts among small and medium size manufacturing firms in Kuching Sarawak.